Gaining Competitive Advantage through Strategic Green Supply Chain Management: From a Literature Review towards a Conceptual Model - S. Maryam Masoumik; Salwa Hanim Abdul-Rashid; Ezutah Udoncy Olugu (International Journal of Supply Chain Management, 2014)
The link between green supply chain practices (GSCPs) and competitive advantages (CAs) is a subject of growing interest amongst academics and practitioners. Despite the theoretical arguments that environmentally conscious practices would give competitive advantages for companies, there is no consensus in empirical research concerning the positive impact of GSCPs on CAs. Due to this lack of clarity in the literature, this study undertakes a comprehensive review to evaluate the circumstances necessary for GSCPs to achieve sustainable CAs. Subsequently, a conceptual model is proposed to elaborate on the causal relationship between GSCPs and CAs. Future research opportunities are recommended to expand on the proposed conceptual model and to address the shortcomings of the existing literature.